THE EFFECTIVENESS OF ONLINE MENTORING IN TRAINING THE COMPETENCY OF SPECIAL EDUCATION TEACHERS IN TEACHING READING SKILLS USING THE BASIC PHONICS METHOD (Proceedings of International Conference on Special Education, 2025)
Special education teachers often face challenges such as limited training opportunities and lack of effective resources when teaching reading skills to students with special educational needs (SEN). This action research study investigates the effectiveness of structured online mentoring in enhancing teachers’ competencies in delivering reading instruction using the basic phonics method. Utilizing Kemmis and McTaggart’s Action Research model (1988), the study involved 25 PPKI (Special Education Integration Program) teachers from various regions of Malaysia with 3 to 15 years of teaching experience. The intervention consisted of two action research cycles, each including planning, implementation, observation, and reflection. Teachers participated in a six- week online mentoring program featuring theoretical modules, guided practice, and video-based feedback. Findings revealed a substantial improvement in teacher knowledge—post-intervention, 44% reported strong understanding compared to 0% before—and a complete increase in practical implementation, rising from 16% to 100% adoption of phonics strategies in classrooms. Moreover, student reading outcomes improved, with teachers reporting enhanced letter-sound recognition and syllable reading skills. The results underscore the potential of structured online mentoring to significantly enhance teacher competencies and student literacy outcomes.